Do as the neighbors do: the impact of social networks on immigrant employment - Fredrik Andersson; Simon M. Burgess; Julia Lane (Institute for the Study of Labor (IZA), 2009)
Substantial immigrant segregation in the United States, combined with the increase in the share of the U.S. foreign-born population, have led to great interest in the causes and consequences of immigrant concentration, including those related to the functioning of labor markets. This paper provides robust evidence that both the size and the quality of an immigrant enclave affects the labor market outcomes of new immigrants. We develop new measures of the quality, or information value, of immigrant networks by exploiting data based on worker earnings records matched to firm and Census information. We demonstrate the importance of immigrant employment links: network members are much more likely than other immigrants to be employed in the same firm as their geographic neighbors. Immigrants living with large numbers of employed neighbors are more likely to have jobs than immigrants in areas with fewer employed neighbors. The effects are quantitatively important and robust under alternative specifications. For example, in a high value network - one with an average employment rate in the 90th percentile - a one standard deviation increase in the log of the number of contacts in the network is associated with almost a 5% increase in the employment rate. Earnings, conditional on employment, increase by about 0.7%.
urn:nbn:de:101:1-20091014990
Keywords: J61; J20; 330; Social networks; immigrant enclaves; labor market intermediaries; Internationale Wanderung; Migranten; Arbeitsmarkt; Arbeitsuche; Soziale Gruppe; Soziales Netzwerk; USA